Upaya Meningkatkan Kemampuan Anak Menghafal Kisah 25 Nabi Melalui Metode Sholawat di TPQ Al Faqih Desa Gadungan Kec Puncu Kab Kediri - zuraidah; Ziyadatul Rif’ah; Shefina Nurlaily3 (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
This service activity is entitled "Efforts to Improve Children's Ability to Memorize the Stories of 25 Prophets Through the Sholawat Method at TPQ Al-Faqih". This activity was carried out by TPQ Al-Faqih children in Gadungan Village, Puncu District, Kediri Regency, considering that many TPQ teachers had difficulty explaining the stories of the Prophets. The purpose of holding this research and community service activity is to introduce and improve the memorization of the Story of the 25 Prophets to the children of TPQ Al Faqih through the sholawat method. Therefore, the researcher intends to do community service in the hope of increasing the ability to memorize the stories of the 25 Prophets so that they can be a provision of knowledge for TPQ Al Faqih children in their environment. In this community service activity, it resulted in a new change in how to memorize with the sholawat method, which can help children memorize the Acts of the 25 Prophets.